2015
DOI: 10.1111/acer.12913
|View full text |Cite|
|
Sign up to set email alerts
|

Adolescent Intermittent Alcohol Exposure: Dysregulation of Thrombospondins and Synapse Formation are Associated with Decreased Neuronal Density in the Adult Hippocampus

Abstract: Background Adolescent intermittent alcohol exposure (AIE) has profound effects on neuronal function. We have previously shown that AIE causes aberrant hippocampal structure and function that persists into adulthood. However, the possible contributions of astrocytes and their signaling factors remain largely unexplored. We investigated the acute and enduring effects of AIE on astrocytic reactivity and signaling on synaptic expression in the hippocampus, including the impact of the thrombospondin (TSP) family of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 58 publications
4
54
1
Order By: Relevance
“…Intermittent access to drugs of abuse results in altered behavioral responses in comparison to continued administration (Marec et al, 2011), and intermittent exposure administration procedures are commonly used to study alcohol effects (Pandey et al, 2015; Risher et al, 2015). Having assessed adaptations in cytokine responses that occur with repeated once-daily exposure to ethanol, we next examined whether the schedule of ethanol exposure would impact cytokine expression patterns in the CNS.…”
Section: Methodsmentioning
confidence: 99%
“…Intermittent access to drugs of abuse results in altered behavioral responses in comparison to continued administration (Marec et al, 2011), and intermittent exposure administration procedures are commonly used to study alcohol effects (Pandey et al, 2015; Risher et al, 2015). Having assessed adaptations in cytokine responses that occur with repeated once-daily exposure to ethanol, we next examined whether the schedule of ethanol exposure would impact cytokine expression patterns in the CNS.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is some evidence that alcohol may uniquely affect astrocytes during this developmental period. Intermittent alcohol exposure during adolescence is associated with changes in TSP expression within the hippocampus (Risher et al, 2015b). As previously mentioned, TSPs are glycoproteins secreted in part by astrocytes which mediate cell and matrix adhesion and are critical regulators of synaptogenesis during CNS development (Christopherson et al, 2005;Eroglu et al, 2009).…”
Section: Alcohol Glia and Neuroimmune Signalingmentioning
confidence: 99%
“…A similar enhanced vulnerability of adolescents was also reported by Broadwater et al (2014) who observed lasting disruptions in neurogenesis and increases in cell death in adult rats after EtOH exposure during adolescence but not following equivalent exposure in adulthood. At the synaptic level, there is recent evidence that adolescent exposure to EtOH results in expression of a greater proportion of immature, more “plastic” synaptic spines in the adult HPC (Risher et al, 2015). Alterations in brain activity in this region were evident in terms of long-term potentiation (LTP), with adults exposed to EtOH during adolescence exhibiting more robust LTP than non-exposed animals, suggesting a surprising enhanced state of synaptic plasticity (Risher et al, 2015).…”
Section: Alcoholmentioning
confidence: 99%
“…At the synaptic level, there is recent evidence that adolescent exposure to EtOH results in expression of a greater proportion of immature, more “plastic” synaptic spines in the adult HPC (Risher et al, 2015). Alterations in brain activity in this region were evident in terms of long-term potentiation (LTP), with adults exposed to EtOH during adolescence exhibiting more robust LTP than non-exposed animals, suggesting a surprising enhanced state of synaptic plasticity (Risher et al, 2015). Electrophysiological studies have revealed long-lasting decreases in slow-wave sleep, as well as attenuations in the P3 component of evoked potentials (Ehlers & Criado, 2010).…”
Section: Alcoholmentioning
confidence: 99%